K-Line Tilt is a Predictor of Postoperative Kyphotic Deformity After Laminoplasty for Cervical Myelopathy Caused by Ossification of the Posterior Longitudinal Ligament. Issue 4 (May 2023) - Sakai, Kenichiro; Yoshii, Toshitaka; Arai, Yoshiyasu; Hirai, Takashi; Torigoe, Ichiro; Inose, Hiroyuki; Tomori, Masaki; Sakaki, Kyohei; Yuasa, Masato; Yamada, Tsuyoshi; Matsukura, Yu; Oyaizu, Takuya; et al.
Study Design: Retrospective single-center study. Objectives: K-line is a decision-making tool to determine the appropriate surgical procedures for patients with cervical ossification of the posterior longitudinal ligament (C-OPLL). Laminoplasty (LAMP) is one of the standard surgical procedures indicated on the basis of K-line measurements (+: OPLL does not cross the K-line). We investigated the impact of K-line tilt, a radiographic parameter of cervical sagittal balance measured using the K-line, on surgical outcomes after LAMP. Methods: The study included 62 consecutive patients with K-line (+) C-OPLL who underwent LAMP. The following preoperative and postoperative radiographic measurements were evaluated: (1) the K-line, (2) K-line tilt (an angle between the K-line and vertical line), (3) center of gravity of the head –C7 sagittal vertical axis, (4) C2–C7 lordotic angle, (5) C7 slope, and (6) C2–C7 range of motion. Clinical results were evaluated using the Japanese Orthopedic Association scoring system for cervical myelopathy (C-JOA score). Results: All the patients had non-kyphotic cervical alignment (CL ≥ 0°) preoperatively; however, kyphotic deformity (CL < 0°) was observed in 6 patients (9.7%) postoperatively. The recovery rate of the C-JOA scores was poor in the kyphotic deformity (+) group (7.8%) than in the kyphotic deformity (−) group (47.5%). The K-line tilt was identified to be a preoperative risk factor in the multivariate analysis, and the cutoff K-line tilt for predicting the postoperative kyphotic deformity was 20°. Conclusions: LAMP is not suitable for K-line (+) C-OPLL patients with K-line tilts >20°.